Gustatory Changes Due To Areca Nut Chewing And Osmf - NISHAT FATIMA ABDUL KHADER; SUJATHA.D (International Journal of Pharma and Bio Sciences, 2015)
Over the past several decades, dental researchers reported different aspects of oral submucous Fibrosis (OSMF). Yet, there is a big lacunae in the present scenario of evidence based dentistry which correlates the role of taste perception among OSMF affected individuals and areca nut chewers. The present study intends to assess and compare different taste perception among areca nut chewing, OSMF and control subjects. Comparative study was adopted to assess and compare the 4 basic tastes: sweet, salt, sour and bitter among 135 out patients attending The Oxford Dental college and Research hospital, Bangalore. A detailed case exemplified using a structured proforma and the taste strips were executed for assessing the taste perception. Statistical analysis was done using SPSS 21.0 software. Statistically significant hyperguesia to sweet (28.89%) and bitter taste (35.56%) among areca nut group and hypoguesia to salty (62.2%) and dysguesia to sour taste (40%) among OSMF patients were observed compared to apparently healthy subjects. The present study remarked hyperguesia to sweet and bitter taste among areca nut chewers and hypoguesia to salty taste followed by bitter, sour and sweet taste among OSMF subjects.